Bio-templated fabrication of lotus root-like Li3V2(PO4)3/C composite from dandelion for use in lithium-ion batteries. Issue 10 (July 2019) - Chen, Yueqian; Xiang, Kaixiong; Zhu, Yirong; Xiao, Li; Chen, Wenhao; Liao, Haiyang; Chen, Xianhong; Chen, Han
Abstract: This work focused on a fabrication of lotus root-like Li3 V2 (PO4 )3 /C composites via a repeated immersion process using the dandelion as a bio-template. The Li3 V2 (PO4 )3 /C composites were characterized using X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The Li3 V2 (PO4 )3 /C composites exhibited various structures that were dependent on the various processing techniques. By increasing immersion of the product to three repetitions, a bundle of dandelion carbon fibers was found to be covered by Li3 V2 (PO4 )3 and formed a perfect lotus root-like structure (D-3). The Li3 V2 (PO4 )3 /C composite (D-V) prepared using the vacuum method displayed a dense scrub board-like structure. However, sample D-3 that was prepared using the novel method, exhibited a capacity of 126.8 mAh g −1 at the 1 C rate, a prominent capacity retention of 96.8% after 2000 cycles at the 15 C rate. The experimental results showed that this unique lotus root-like structure is beneficial for improving the capability and cycling stability.